ABSORPTION OF LOCAL LABOR ON THE OIL AND GAS SECTOR IN THE JAMBARAN TIUNG BIRU AREA BOJONEGORO REGENCY - Andria Widiana; Moehadi; Fahrizal Taufiqqurrachman (SEAN Institute, 2023)
The natural oil and gas industry plays a rol in pumping up Bojonegoro’s economic growth chart so that people can find it easier to get work. This study ains to fnd out how many local residents are absorbed into the workforce in the jambaran tiung biru area. Respndents of this study ate worker in Jambaran Tiung Biru. The analysis technique used is swot analysis. The result of thr study show that the Jambaran Tiung Biru area is quadrant I, so the strategy that can be carried out is an aggressive strategy, where this aggressivw strategy requires companies and workforce to focus on; (1) wase of getting jobs to reduce unemployment for local resident (2) the promised salary is quite lage if you work according to your ezpertise (3) get a job according to your expertties of there is training (4) good performance will easily extend the contract.